THE MAIN DIRECTIONS OF THE DIGITAL PROFILE CONCEPT DEVELOPMENT. FOREIGN EXPERIENCE AND DEVELOPMENT PROSPECTS - A. V. Badina; M. N. Oreshina (Вестник университета)
An approach to solving a comlex and urgent problem facing state and near-state agencies has been described: to provide popular modern services to citizens, while reducing operating costs through the use of digital technologies to improve citizen service and develop more effective ways to work. At the moment, this is achievable by developing a unified information base for the provision of public services, based on the creation of a digital citizen profile. A comparative review of international experience in the field of digitalization of the process of interaction between citizens and government structures has been presented. In accordance with the digitalization programs launched in many countries almost simultaneously, many commercial and social projects are being developed. All of them become available when using complex analytical tools for processing Big data and a Unified identification and authentication system.